2019
DOI: 10.1371/journal.pone.0225763
|View full text |Cite
|
Sign up to set email alerts
|

Men and women differ in their perception of gender bias in research institutions

Abstract: There is extensive evidence of gender inequality in research leading to insufficient representation of women in leadership positions. Numbers revealing a gender gap in research are periodically reported by national and international institutions but data on perceptions of gender equality within the research community are scarce. In the present study, a questionnaire based on the British Athena Survey of Science, Engineering and Technology (ASSET 2016) was distributed among researchers working in Spain. Consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 29 publications
5
31
1
2
Order By: Relevance
“…Another comparative study conducted among the nonmedical academicians in Spain and the UK demonstrated that women perceived more gender inequality in areas of invitation to conferences as speakers, receiving scientific awards, representation on editorial boards of scientific publications, receiving citations, invitation to be a reviewer, promotions and leadership positions, whereas men did not perceive such extensive discrimination [14]. Similarly, Handley et al documented that men didn't admit the existence of gender bias in science as women did [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another comparative study conducted among the nonmedical academicians in Spain and the UK demonstrated that women perceived more gender inequality in areas of invitation to conferences as speakers, receiving scientific awards, representation on editorial boards of scientific publications, receiving citations, invitation to be a reviewer, promotions and leadership positions, whereas men did not perceive such extensive discrimination [14]. Similarly, Handley et al documented that men didn't admit the existence of gender bias in science as women did [15].…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, women (and maybe other under-represented minorities) may feel less capable, less prepared, or have less self-confidence to carry out certain roles [1]. Also, they may feel that they do not belong in that environment.…”
Section: Social Roles Theorymentioning
confidence: 99%
“…The explanation about the imbalance suggests that bias against women plays an important role in generating these differences [35,38,39]. There are conscious or unconscious biases, subtle or blatant, which have a great impact on the absence of female scientific models [1,40]. The under-representation of women in science is a multi-dimensional problem.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations